2010
DOI: 10.1080/13602380701517048
|View full text |Cite
|
Sign up to set email alerts
|

The impact of task and outcome interdependence and self-efficacy on employees' work motivation: an analysis of the Malaysian retail industry

Abstract: This study investigates the relationship between task and outcome interdependence and self-efficacy on employees work motivation in Malaysia, by looking at one of the state's retail industries as a case in point. The study focused on two forms of interdependence, namely task interdependence (works execution) and outcome interdependence (compatibility of co-workers' performance), while work motivation looked at employees' cooperation and collective effort. The retail industry was chosen because of its importanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Based on my review of extant research on work motivation, I developed and tested the inter-relationships among work attitudes and extra-role work-related behaviours in a comprehensive framework. In addition to affording insights into the complex inter-relationships amongst these concepts, this study addresses four significant gaps identified in the work motivation and organizational behaviour literature: (1) it examines how affective commitment is related to behavioural efforts, specifically organizational citizenship behaviours (Boezeman & Ellemers, 2008); (2) it utilizes reliable and validated instruments (Toode et al, 2011); (3) it comprises a fairly large sample to have empirical support for generalizability (Ayupp & Kong, 2010); and (4) by using a cross-sector design, it is generalizable to nurses actively working in hospitals, the community, and long-term care settings in Ontario, Canada (Park, 2010).…”
Section: Purposementioning
confidence: 99%
See 1 more Smart Citation
“…Based on my review of extant research on work motivation, I developed and tested the inter-relationships among work attitudes and extra-role work-related behaviours in a comprehensive framework. In addition to affording insights into the complex inter-relationships amongst these concepts, this study addresses four significant gaps identified in the work motivation and organizational behaviour literature: (1) it examines how affective commitment is related to behavioural efforts, specifically organizational citizenship behaviours (Boezeman & Ellemers, 2008); (2) it utilizes reliable and validated instruments (Toode et al, 2011); (3) it comprises a fairly large sample to have empirical support for generalizability (Ayupp & Kong, 2010); and (4) by using a cross-sector design, it is generalizable to nurses actively working in hospitals, the community, and long-term care settings in Ontario, Canada (Park, 2010).…”
Section: Purposementioning
confidence: 99%
“…Shared goals, linking employee goals and company goals, has been shown to reinforce work motivation (Ayupp & Kong, 2010), where pursuing set goals reduces the negative effects of high demands (Tadic, Bakker, & Oerlemans, 2013). High demands refer to jobs that are onerous, over-challenging, or require an unreasonable amount of effort.…”
Section: Scoping Reviewmentioning
confidence: 99%
“…Abdullah et al, 2010;Nankervis, Compton, & Baird, 2008). By providing individualized concern for subordinates' personal and familial well-being, benevolent leaders may build a favorable leader-employee relationship and subsequently reduce the likelihood of employees leaving their job (Ayupp & Kong, 2010). On the positive note, employees would have responded to the benevolent leaders by contributing more on their work in exchange due to the value they perceived from the relationship (Farh et al, 2006;Farh & Cheng, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, people with high self-efficacy will try harder to handle the challenges. This case has been shown in the research result proven that self-efficacy plays an important role in coping worker motivation to finish challenging workrelated with reaching certain goals (Ayupp & Kong, 2010).…”
Section: Introductionmentioning
confidence: 85%